2022
DOI: 10.3892/ol.2022.13495
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of sarcopenia as determined by bioelectrical impedance analysis in patients with advanced pancreatic cancer receiving gemcitabine plus nab‑paclitaxel: A retrospective study

Abstract: Sarcopenia often affects patients with various types of cancer, and has been reported to affect patient prognosis and therapeutic effects. However, to the best of our knowledge, there are no reports on the relationship between gemcitabine plus nab-paclitaxel combination therapy (GnP) and sarcopenia in patients with unresectable pancreatic cancer. The present study analyzed the relationship between overall survival (OS), progression-free survival (PFS), response rate, disease control rate, adverse events (AEs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Gupta et al reported that the phase angle used as an index for evaluating cell membranes and intra-and extracellular water balance was a strong prognostic indicator in advanced PDAC, and patients with a phase angle > 5.0° had a signi cantly better prognosis than those with a phase angle < 5.0° (MST, 10.2 vs 6.3 months, p = 0.02) [26]. Additionally, Tozuka, et al revealed that SMI obtained by BIA may be a predictor of treatment response and prognosis in patients with advanced PDAC who underwent gemcitabine plus nab-paclitaxel combination therapy, and the progression-free survival in the sarcopenia group was signi cantly lower compared with that of the non-sarcopenia group (4.4 vs 6.4 months, p = 0.03) [27]. In the current study, the SMM did not change signi cantly, while the BFM changed signi cantly from preoperatively to 12 months postoperatively; therefore, we speculated that the rate of BFM change may be a sensitive re ection of malnutrition related to prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al reported that the phase angle used as an index for evaluating cell membranes and intra-and extracellular water balance was a strong prognostic indicator in advanced PDAC, and patients with a phase angle > 5.0° had a signi cantly better prognosis than those with a phase angle < 5.0° (MST, 10.2 vs 6.3 months, p = 0.02) [26]. Additionally, Tozuka, et al revealed that SMI obtained by BIA may be a predictor of treatment response and prognosis in patients with advanced PDAC who underwent gemcitabine plus nab-paclitaxel combination therapy, and the progression-free survival in the sarcopenia group was signi cantly lower compared with that of the non-sarcopenia group (4.4 vs 6.4 months, p = 0.03) [27]. In the current study, the SMM did not change signi cantly, while the BFM changed signi cantly from preoperatively to 12 months postoperatively; therefore, we speculated that the rate of BFM change may be a sensitive re ection of malnutrition related to prognosis.…”
Section: Discussionmentioning
confidence: 99%